Factors affecting the English language competency among minority nationality junior high school students: a qualitative inquiry - Zhao, Panzhen; Hassan, Aminuddin; Burhanuddin, Nur Aimi Nasuha; Shi, Long (Society for Research and Knowledge Management, 2025)
In the context of globalization, competency in the English language is a key in securing educational attainment and social promotion. However, minority nationality junior high school students in remote areas in China still face challenges in learning the English language. This study explored the English learning experiences among Zhuang, Miao, Yi, and Gelao middle school students in Guangxi, focusing on the factors influencing their language development in light of Bronfenbrenner's (1979) Ecological Systems Theory. A qualitative case study design was employed, with data collected through semi-structured interviews with ten students, ten parents, and six teachers at a multi-nationality junior high school. Thematic analysis revealed that socioeconomic restrictions, limited English exposure, and the absence of culturally responsive pedagogy were the main obstacles in language development. Notably, home-school collaboration through WeChat was a main facilitator, supporting student motivation and language use outside the classroom. In addition, internal motivation and practical application of English by the students were crucial in their learning outcomes. These findings highlight the need for culturally responsive pedagogy, more educational resources, and digital technology in bridging linguistic and educational gaps. The study contributes to inclusive and quality education by demonstrating the interaction among sociocultural, economic, and educational factors in influencing minority nationality students' English language competency. Given that the study was conducted in a single school, future studies should be extended to various ethnic groups and areas in order to paint a more holistic picture of minority nationality students' English learning experiences.